Enhancing Appraisal Methods to Support Sustainable Transport and Land Use Policies - Page, Matthew; Kelly, Charlotte; May, Anthony; Jones, Peter; Forrester, John (European Journal of Transport and Infrastructure Research, 2009)
This paper reports on the results of the part of the DISTILLATE programme which looked at the process of appraisal and how this affects UK local authorities. Initial surveys suggested that local authorities were concerned that formal appraisal methods represented a barrier to the implementation of more sustainable land use and transport schemes. Their concerns included some of the technical aspects of appraisal and the weight given to some elements, the applicability of techniques to small schemes and some types of measure as well as the ability to assess the distributional impacts of proposals. Responding to these concerns, the project looked in more detail at the reasons for these concerns and at the use of appraisal within the political process of decision making. It developed a simple, transparent technique for analysing small schemes and two methods for assessing the distributional impacts of proposals, both on individuals and agencies. Finally it developed guidance from first principles on the specification of appraisal processes.